Antinociceptive activities of crude methanolic extract and phases, n-butanolic, chloroformic and ethyl acetate from Caulerpa racemosa (Caulerpaceae) - Souza,Everton T. (2009)
In this study, we attempted to identify the possible antinociceptive actions of n-butanolic phase, chloroformic phase, ethyl acetate phase and crude methanolic extract obtained from Caulerpa racemosa. This seaweed is cosmopolitan in world, mainly in tropical regions. The n-butanolic, chloroformic, ethyl acetate phases and crude methanolic extract, all administered orally in the concentration of 100 mg/kg, reduced the nociception produced by acetic acid by 47.39%, 70.51%, 76.11% and 72.24%, respectively. In the hotplate test the chloroformic and ethyl acetate phase were activite in this models. In the neurogenic phase on formalin test, were observed that crude methanolic extract (51.77%), n-butanolic phase (35.12%), chloroformic phase (32.70%) and indomethacin (32.06%) were effective in inhibit the nociceptive response. In the inflammatory phase, only the ethyl acetate phase (75.43%) and indomethacin (47.83%) inhibited significantly the nociceptive response. Based on these data, we can infer that the ethyl acetate phase shows a significant anti-inflammatory profile, whose power has not yet been determined. However, pharmacological and chemical studies are continuing in order to characterize the mechanism(s) responsible for the antinociceptive action and also to identify other active principles present in Caulerpa racemosa.